Tiktoker's Online Personal Branding: A Dramaturgy Study of @Toyib Alwi - Maqpiroh, Lailatul; Palupi, P (Universitas Muhammadiyah Surakarta, 2022)
Purpose: The objective of this research is to investigate how the owner of the TikTok account @Toyib Alwi with 2.4 million followers conducts personal branding. Methodology: This study employed a qualitative methodology with a descriptive approach to provide a thorough explanation of how TikTokers, specifically @Toyib Alwi, establish their personal brand through TikTok social media. Results: This study reveals that Toyib utilized Montoya's eight personal branding concepts, including the law of specialization, the law of leadership, the law of personality, the law of distinctiveness, the law of visibility, the law of unity, the law of persistence, and the law of goodwill, to form his personal branding. Applications/Originality/Value: This study is significant as it delves into the circumstances under which TikTok is utilized to earn or monetize. Aspiring to monetize their accounts, TikTok account owners must pay attention to their personal branding.